Zewnętrzne źródła finansowania inwestycji infrastrukturalnych jednostek samorządu terytorialnego (JST) - Banaszczak-Soroka, Urszula (The External Sources of Financing Infrastructural Investments of the Local Administrative Units (LAU), 2005)
One of the main purposes of LAU is to provide proper conditions of life that manifests itself, among others, in the saturation of social and technical infrastructure. The estimations of the Agency of Communal Development indicates that achieving the European standard of communal infrastructure alone spending at least PLN 64 billion, which is very close to yearly incomes of all LAUs in Poland. The realization of tasks from this area is restricted by the regulations concerning debts of local governments. This situation demands searching for diverse sources of financing which allows minimizing mortgage costs. It is an essential part of the financial policy of local governments to have skills to accumulate different sources of financing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 298-302